VIEWS OF TEACHERS ON THE USE OF ICT AND POSSIBILITIES OF FURTHER EDUCATION - BÁNESZ, Gabriel (Trends in education, 2011)
The goal of the KEGA project "Verification of the video conferencing system and distant technologies in applications" is to analyze the possibilities of the video conferencing systems and distant technologies use in primary and secondary schooling. At the same time, the aim is to specify the minimum technical and organisational requirements for the successful use of these systems and multimedia technologies as well as for designing educational programmes. The paper presents the views of teachers on the use of these technologies in practice and on the possibilities of their further education.
Keywords: further education; information and communication technologies; multimedia technologies; teacher training.